Evaluasi Implementasi Protokol K3 terhadap Keselamatan dan Produktivitas Operasional Mesin Kapal di Industri Maritim - Surjaman, Febria (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Evaluating the implementation of Occupational Health and Safety (OHS) protocols in the operation of ship machinery is a crucial aspect of the maritime industry. This study examines the impact of OHS protocol implementation on safety and productivity in this sector through a literature review method. The OHS protocols applied in the maritime sector aim to minimize the risk of work accidents and enhance operational efficiency of ships. This review includes an analysis of previous research on the effectiveness of OHS protocols, including accident reporting systems, worker training, and ship machinery maintenance. Findings from this study indicate that strict implementation of OHS protocols can reduce accident rates, improve compliance with safety regulations, and enhance ship operational productivity. Additionally, the study highlights challenges faced in the implementation of OHS protocols, such as inadequate training and high costs. By understanding these impacts and challenges, the maritime industry can optimize OHS strategies to improve safety and efficiency in ship machinery operations.